Analisis Return on Aset dan Debt to Equity Ratio pada Nilai Perusahaan - Fitria Fitria; Rahmat Rahmat; Adriansyah Adriansyah; Vannesa Vannesa (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the return on assets and Debt to Equity ratio on firm value. This research method is quantitative. In this study there are two independent variables, namely Return on Assets and Debt to Equity, and the dependent variable is firm value. For the population in this study is PT. Bank Rakyat Indonesia, Tbk for the 2012-2021 period, as well as the sampling technique used in this study, purposive sampling method. The results of the study show that Return on Assets (ROA) has a significant negative effect on firm value, and this is contrary to the results obtained by several previous researchers and the Debt Equity Ratio (DER) has a significant negative effect on firm value. The results of the study simultaneously show that Return on Assets (ROA) and Debt Equity Ratio (DER) have a significant negative effect on firm value. This is not in line with the results stated by several previous researchers. Keywords: Debt to Equity Ratio, Firm Value, Return on Assets